TELAAH KONSEP JAMINAN DALAM AKAD MUDHARABAH DI PERBANKAN SYARIAH - Hilman Jayadi; Darlin Rizki; Husnul Khatimah (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2022)
The guarantee provisions in Indonesian positive law cannot be simply applied to Islamic banking, without reviewing and analyzing the provisions of Islamic law, because Islamic banks still have to implement sharia complieant systems and operations. The purpose of this study is to find out more about the status of guarantees in mudharabah profit sharing contracts in Islamic banking. Knowing the ideas in the development of guarantees from the perspective of positive law that applies in Islamic banks, and their compatibility with fiqh studies. This research is a qualitative library research. Data were collected from a number of publications related to the research topic, then the data were interpreted and analyzed descriptively. The results of this study indicate that the legitimacy of Islamic law allows taking material guarantees for the mudharabah contract as a guarantee against negligence or violations that may be committed by trust holders such as mudarib. Collateral is an important thing to be included in financing in Islamic banking with the reason of avoiding violations that may occur by the debtor. The permissibility or necessity of collateral in sharia law is also explained by an Islamic figure, namely Sheikh 'Ali al-'Adawi who asserts that it is legal to take collateral to guarantee trust contracts against moral hazard (borrower moral hazard) that may be carried out by the trust holder.